Capital Redefined A Commonist Value Theory for Liberating Life - HOSSEINI, S A Hamed (Rethinking Globalizations, 2024)
Capital Redefined presents a unique perspective on the nature of "capital," departing from the prevailing reductionist accounts. Hosseini and Gills offer an expanded perspective on Marxian value theory by addressing its main limitations and building their own integrative value theory. They argue that the current understanding of "value" must be re-examined and liberated from its subservient ties to capital while acknowledging the ways in which capital appropriates value. This is achieved by differentiating between "fetish value" created by capital and "true value" generated through various commons-based forms of coexistence. The authors propose a defetishization of value by rejecting the commonly accepted idea of its objectivity. They introduce their "commonist value theory," which redefines capital as both the product and process of perverting the fundamental commoning causes of true value into sources of fetish value. Capital is theorized through a "modular" framework, where multiple intersecting processes constitute a comprehensive power structure, a "value regime," representing an unprecedented degree of the domination of capital over life. Their theory reconciles two apparently incompatible views on the notion of value. One view encompasses all inputs involved in capitalist value production and conflates intrinsic and commodity values. The other warns against this conflation as it treats capital as an entity tightly associated only with commodity production and wage labor. The authors believe that establishing alternative forms of value creation based on normative principles of living in commons is crucial as an analytical base for criticizing existing power structures and economic systems. The book offers a theoretical foundation for transforming our life worlds toward "post-capitalist" futures. It appeals to scholars and students in various fields, such as political economy, capitalism, and post-capitalist studies, economic and political sociology, globalization, development studies, social ecology, and ecological philosophy.